HUBUNGAN KUALITAS PERNIKAHAN DENGAN KEBAHAGIAAN DAN KEPUASAN HIDUP PRIBADI: STUDI PADA INDIVIDU DENGAN USIA PERNIKAHAN 1-5 TAHUN DI BANDUNG - Kendhawati, Lenny; Purba, Fredrick Dermawan (Faculty of Psychology, Diponegoro University, 2019)
Marriage is proven to be related to health and well-being of those involved in it. However, the status of marriage is not the most important, but how the quality of the marriage is the key to its positive effects. This study aims to examine a relationship between marital quality with happiness and life satisfaction. Data collection was conducted on 189 participants who have married with less than five years, said to be a critical period, which are living in the city of Bandung. The marital quality was measured using the Quality Marriage Index/QMI (6 items; Î±= .91), happiness was measured using the Happiness Thermometer at three time points (3 items; Î±= .83), and life satisfaction was measured using the Self-Anchoring Cantril Striving Scale at three time points (3 items; Î±= .47). The Spearman correlation test found that there was a significant positive relationship between the marital quality and happiness at three time points: today (rs= 0.431), last month (rs= 0.409), and throughout life (rs= 0.415) and life satisfaction at two time points: now (rs= 0.460) and next five years (rs= 0.281). In addition, life satisfaction of five years ago when subjects were still single was reported to be significantly lower compare to their life satisfaction this moment and predicted five years from now (p<0.001). These findings suggest that married couple giving more attention to improving the quality of their marriage relationship in order to be happier and satisfied with their life.